Abdominal Cocoon in an Adolescent Male - Shakya, VC; Agrawal, CS; Rajbanshi, SK; Pradhan, A; Khaniya, S; Adhikary, S (Kathmandu University Medical Journal, 2014)
Abdominal cocoon is an uncommon peritoneal condition characterized by partial or complete encasement of small bowel by a thick rind of fibrous tissue and adhesions. Only few cases of this disease have been reported in world literature. The etiology of this condition is unknown, and most often it is found in adolescent girls from tropical or subtropical countries, and usually diagnosed incidentally on exploration. Surgery (membrane dissection and extensive adhesiolysis) is the treatment of choice. Here, we report a case of abdominal cocoon in a 20-year-old male patient, with a brief review of the literature. DOI: http://dx.doi.org/10.3126/kumj.v10i4.11009 Kathmandu Univ Med J 2012;10(4):83-86